X(2x-5)=(2x+5)(x-4)

Simple and best practice solution for X(2x-5)=(2x+5)(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(2x-5)=(2x+5)(x-4) equation:



X(2X-5)=(2X+5)(X-4)
We move all terms to the left:
X(2X-5)-((2X+5)(X-4))=0
We multiply parentheses
2X^2-5X-((2X+5)(X-4))=0
We multiply parentheses ..
2X^2-((+2X^2-8X+5X-20))-5X=0
We calculate terms in parentheses: -((+2X^2-8X+5X-20)), so:
(+2X^2-8X+5X-20)
We get rid of parentheses
2X^2-8X+5X-20
We add all the numbers together, and all the variables
2X^2-3X-20
Back to the equation:
-(2X^2-3X-20)
We add all the numbers together, and all the variables
2X^2-5X-(2X^2-3X-20)=0
We get rid of parentheses
2X^2-2X^2-5X+3X+20=0
We add all the numbers together, and all the variables
-2X+20=0
We move all terms containing X to the left, all other terms to the right
-2X=-20
X=-20/-2
X=+10

See similar equations:

| 3x-10=5(x+2)-2x | | -0.8x=64 | | 4/2x-1=3/11 | | 5(4+2x)=0 | | 8-3(-12x+2)=0 | | 8=2/3(9x-6) | | 14u-13u-1=17 | | 2.6v=7.5 | | 10x-2x-9=-45+12x | | X+2x+3x+3=21 | | 2y+6y=-8 | | 2x-35+5x=0 | | 3(2x-7)=44 | | 2/5x+2=5 | | 2x^=32 | | 5x6/3+7=-1 | | 2(5+5x)=30 | | X(y-4)+4y=2598 | | 2x-3=1/2(2x+6) | | 3-2x+4x+6x=9 | | 5x^2-44x+150=11x | | 3-2x+4x+6x=8 | | 25x-6=10x+86 | | (y/5)^2=121 | | 2.6*v=7.5 | | 7x+82=348 | | 7x+84=348 | | 16w+7w-5w=0 | | 7x+86=348 | | 2.5x-1=10-7.5x | | −94v+45=78−94v+45=78 | | 7x+88=348 |

Equations solver categories